Factors affecting household’s access to water supply in varied income residential areas in parts of Lagos metropolis - Akoteyon, Isaiah Sewanu (Bulletin of Geography. Socio-economic Series, 2019)
Access to water is vital for healthy living. The study examined factors affecting household’s access to water supply in varied income residential areas in parts of Lagos metropolis. Data used was obtained from 200 household’s using systematic sampling technique. The result shows the dominance of improved water source in the high/medium income residential areas. Households in the medium income areas recorded the highest access based on distance and safe water supply. The principal component explains 77.41% of the variance with three components namely; water access, demographic and economic attributes. The ANOVA reveals three significant variables namely main water source, income and cost [F (3, 196) = 35.159, p <. 000]. The regression equation model is Y= 2.059 + 0.307MWS + 0.286INM + 0.164CST. Main water source, income and cost are the factors affecting access to water in the study area. Rainwater harvesting and extension of water trunks were recommended.